Residential satisfaction of long-term public rental housing - KIM, Jinhui (KDI School, 2017)
The objective of this study is to investigate determinants to affect the residential satisfaction of long-term public rental housing. This study developed all fundamental variables using the database of “Residential satisfaction of residents in public rental housing” that the LH carried out a survey of residents in National Rental Housing throughout the country in 2014. And this study categorized determinants to affect residential satisfaction into six major factors such as product physical factor, residential environment factor, operating service factor, repair service factor, economic factor, and personal factor. Using confirmatory factor analysis, two group comparison analysis, and regression analysis, this study analyzed effects of each factor and determinant on overall residential satisfaction. According to the results of simple regression analyses of five factors except personal factor, economic factor had strongest correlation with residential satisfaction, and product physical factor, operating service factor, residential environment factor and repair service factor followed in order. In terms of specific variables, gender and the number of household members didn’t affect residential satisfaction, and age and household income slightly affected residential satisfaction. And other various variables all influenced residential satisfaction. Especially, maintenance fee and rent level highly affected residential satisfaction compared to other variables relevant to housing design, environment, and service. Factors and independent variables in this study were subjective data except personal factor, so it facilitated comparisons between determinants. Also, based on the results of factor analyses and multi-regression analyses, this study found that housing physical features didn’t have distinguishable effects on residential satisfaction from environment and neighborhood features, and those variables were highly correlated with each other. And this study found that operating service factor and repair service factor also had strong correlation, and didn’t have meaningful differences related to effects on residential satisfaction. Finally this study provides implication for residential satisfaction of long-term public rental housing in Korea. This study suggests that the crucial determinants to affect overall residential satisfaction is the economic factor such as rent level and maintenance fee, and economic factor should be significantly handled to improve residential satisfaction of long-term public rental housing.
Thesis(Master) --KDI School:Master of Development Policy,2017